2018
DOI: 10.31248/jasvm2018.076
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of growth performance, immunity and disease resistance in Nile tilapia, Oreochromis niloticus, by using dietary probiotics supplementation

Abstract: This study evaluated the effect of probiotics on the growth performance, some immunological, biochemical and hematological parameters of Nile tilapia. Eight weeks feeding trials were conducted to examine the effect of three types of probiotics, multi-strain probiotics (6×10 7 cfu/g), Bacillus subtilis (1×10 11 cfu/g) and Saccharomyces cerevisiae (2.6×10 10 cfu/g) in commercial names Protexin, Biogen-S and Diamond V respectively. Nile tilapia (24±0.02 g) was fed probiotic-incorporated diets as well as control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Serum ALT levels decreased significantly with the first diet. Consistent with our results, [34] used three types of probiotics, multi-strain probiotics (6 × 107 cfu/g), Saccharomyces cerevisiae (2.6 × 1010 cfu/g) and Bacillus subtilis (1 × 1011 cfu/g) and in the diet of Nile tilapia, and showed that ALT and AST levels were reduced in fish fed with different probiotic species. In addition [37] reported the addition of a Nutrasexylam © enzyme supplement containing a mixture of α-amylase (40,000 /g) and βxylanase (6,300u/g) had no adverse effect on fish health and that the concentrations of AST and -ALT in plasma was normal.…”
Section: Haemato-biochemical Changessupporting
confidence: 87%
See 1 more Smart Citation
“…Serum ALT levels decreased significantly with the first diet. Consistent with our results, [34] used three types of probiotics, multi-strain probiotics (6 × 107 cfu/g), Saccharomyces cerevisiae (2.6 × 1010 cfu/g) and Bacillus subtilis (1 × 1011 cfu/g) and in the diet of Nile tilapia, and showed that ALT and AST levels were reduced in fish fed with different probiotic species. In addition [37] reported the addition of a Nutrasexylam © enzyme supplement containing a mixture of α-amylase (40,000 /g) and βxylanase (6,300u/g) had no adverse effect on fish health and that the concentrations of AST and -ALT in plasma was normal.…”
Section: Haemato-biochemical Changessupporting
confidence: 87%
“…This match with those of [33] who showed that protease enzyme addition increased total protein levels, globulin, and albumin in the serum of Nile tilapia fed diets with high incorporation levels of cotton seed meal and supplemented with exogenous protease. Similarly, [34] used three types of probiotics, multi-strain probiotic (6 × 107 cfu / g), Bacillus subtilis (1 × 1011 cfu / g), and Saccharomyces cerevisiae (2.6 × 1010 cfu / g) in Nile tilapia diet and showed an increase in total protein and globulin in fish fed different probiotic species.…”
Section: Haemato-biochemical Changesmentioning
confidence: 99%
“…Blood parameters are an important stressor indicator and a health determining factor in aquatic animals (Cho et al., 2015; Dowidar et al., 2018). The temperature has been considered as a major factor impacting the haematology and immunology of finfish (De et al., 2019; Lulijwa et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The world's total tilapia production reached approximately 6 million tons in 2020 ( Guenard, 2020 ). The advantageous features of tilapia most importantly faster growth, extreme tolerance capacity to hostile environments, high disease resistivity along with high survival rate make it a predominant culture species ( Alam et al., 2014 ; Dowidar et al., 2018 ; Hossain et al., 2022 ). However, the main obstacle in tilapia culture is its early sexual maturity and frequent spawning in the culture system ( Lind et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%